Ego-protect in the structure psychological welfare (Actual Problems of Psychology in Educational Institutions, 2019)
The article presents a theoretical analysis of the problem ofpsychological well-being. The classification of approaches to the understandingof this phenomenon by representatives of Western psychology is considered.The importance of protective mechanisms in resolving internal and externalcontradictions of the personality is noted. Also focused on the definition of thephenomenon of Ego-protection as an important unconscious mechanism for theregulation of behavior and human activity. The comparison of views on the useof protective mechanisms as a way of solving difficulties by illusory attenuationof perceived stress and phenomenon is presented, which leads to the formationof various interpersonal conflicts.
Keywords: ​ psychological well-being; mechanisms of Ego-defense; internal conflict; contradictions; self-realization; positive and negative affects